Kriteria Diagnostik dan Pendekatan Terapeutik pada Pasien dengan DIslipidemia Pediatri - nickyta; Dyah Wulan Sumekar Rengganis Wardani; Anggraeni Janar Wulan (CV. Jasa Sukses Abadi, 2022)
Dyslipidemia or hyperlipoproteinemia is a quantitative change in the concentration of total cholesterol, its fraction, or just triglycerides in plasma. In addition, there is ample evidence to support that pediatric dyslipidemia is associated with atherosclerosis in adulthood. To reduce cardiovascular risk in adulthood, early identification and treatment is needed to reduce morbidity and mortality. Dyslipidemia itself can occur due to changes in primary lipoprotein metabolism due to genetic (primary) causes or other pathologies such as the result of accumulation of exogenous (secondary) factors. Therefore, mixed dyslipidemia results from genetic and environmental associations with risk factors for cardiovascular disease. However, lipid metabolism screening in pediatrics is not carried out in a targeted manner, causing problems where the outcome is not generally accepted. In addition, no one knows the effect of long-term pharmacological therapy. Therefore, this study aimed to review the various available literature resources on pediatric dyslipidemia to present data on a structured approach to pediatric dyslipidemia that focuses on screening, atherosclerotic risk stratification, and therapeutic approaches.